Moving Up Trainees’ Motivation for Using On-job Training: Relationship between Leaders’ Support and Trainees’ Motivation for Learning - Ismail, Azman; Asha'ari, Maryam Jamilah; Foboy, Siti Nurul Afiqah; Hanafi, Wan Noordiana Wan; Mohamad Nor, Azmawaty; Husin, Tehsapuan (The South East Asian Journal of Management, 2024)
Research Aims: This study examined the relationship between leaders’ support and trainees’ learning outcomes and the relationship between leaders’ support, trainees’ motivation for learning, and trainees’ motivation for using on-job training. Design/Methodology/Approach: A cross-sectional research design was employed to collect 226 self-report questionnaires from employees at military healthcare organisations in Peninsular Malaysia. The SmartPLS was used to assess the quality of the measurement model and test the structural model. Research Findings: This study confirmed that trainees’ motivation for learning is an essential mediating construct in the relationship between leaders’ support and trainees’ motivation for using on-job training. Theoretical Contribution/Originality: This study disclosed that trainees’ motivation for learning can indirectly affect the relationship between leaders’ support and trainee’s motivation to use on-job training. This outcome was consistent with and extended the prior studies conducted in Southeast Asia and other countries. Managerial Implication in the South East Asian context: The findings can help leaders understand the multidimensional perspectives of trainees’ motivation for learning construct and the importance of leaders and members at various hierarchical levels to maintain and enhance their organisational performance and competitiveness in 21st-century globalisation and uncertainty economy. Research Limitations & Implications: Methodological and conceptual constraints must be considered to improve future studies.